2013
DOI: 10.1371/journal.pone.0077599
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Model of the Horse Gut Microbiome Enables Identification of Lactate-Utilizing Bacteria That Differentially Respond to Starch Induction

Abstract: Laminitis is a chronic, crippling disease triggered by the sudden influx of dietary starch. Starch reaches the hindgut resulting in enrichment of lactic acid bacteria, lactate accumulation, and acidification of the gut contents. Bacterial products enter the bloodstream and precipitate systemic inflammation. Hindgut lactate levels are normally low because specific bacterial groups convert lactate to short chain fatty acids. Why this mechanism fails when lactate levels rapidly rise, and why some hindgut communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 45 publications
3
62
0
5
Order By: Relevance
“…Those authors found a particularly high increase of the relative abundance of Veillonella sp. which is a lactateutilizing bacteria genus (Biddle et al, 2013). In the current study faecal LPS concentration was positively correlated with the lactate-utilizing bacteria count in the proximal hindgut.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors found a particularly high increase of the relative abundance of Veillonella sp. which is a lactateutilizing bacteria genus (Biddle et al, 2013). In the current study faecal LPS concentration was positively correlated with the lactate-utilizing bacteria count in the proximal hindgut.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the mechanisms by which regulatory systems within Bacteroidetes PULs respond to carbohydrates and how signals are transduced into gene expression are not fully understood. In particular, a complete structural and functional portrait of these complex membrane-spanning systems, as well as a detailed understanding of the genetic signatures targeted by these proteins (135), will help fill a significant gap in our understanding of how PULs are regulated and may help usher in an era of designer communities and personalized intestinal medicine (136)(137)(138). Recently, a series of cisencoded small RNAs were discovered in association with a subset of PULs in Bacteroides fragilis (139).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…High blood lactate levels may lead to acidosis, a phenomenon associated with irritated or damaged mucosa (Al Jassim et al 2005). Acidosis often leads to laminitis, which is symptomatic of toxins secreted from the GIT into the blood stream (Biddle et al 2013) or colic (Pagan 1998), but this is usually associated with blood glucose concentrations in excess of 200 mg dl −1 (Thrall et al 2004). …”
Section: Discussionmentioning
confidence: 99%